Cx43-mediated sorting of miRNAs into extracellular vesicles - Martins-Marques, Tânia (2022)
Through the exchange of lipids, proteins, and nucleic acids, extracellular vesicles (EV) allow for cell-cell communication across distant cells and tissues to regulate a wide range of physiological and pathological processes. Although some molecular mediators have been discovered, the mechanisms underlying the selective sorting of miRNAs into EV remain elusive. Previous studies demonstrated that connexin43 (Cx43) forms functional channels at the EV surface, mediating the communication with recipient cells. Here, we show that Cx43 participates in the selective sorting of miRNAs into EV through a process that can also involve RNA-binding proteins. We provide evidence that Cx43 can directly bind to specific miRNAs, namely those containing stable secondary structure elements, including miR-133b. Furthermore, Cx43 facilitates the delivery of EV-miRNAs into recipient cells. Phenotypically, we show that Cx43-mediated EV-miRNAs sorting modulates autophagy. Overall, our study ascribes another biological role to Cx43, that is, the selective incorporation of miRNAs into EV, which potentially modulates multiple biological processes in target cells and may have implications for human health and disease.